Publications and new products (Journal of EAHIL, 2024)
Dear all,for this issue’s “Publications and new products” column I’ve searched the web and selected news and articles regarding several current topics which I hope would be of your interest.I would also like to take this occasion to wish you and your family all the best for the New Year.